Applying Hirāba in Islamic Criminal Law to Curb Armed Banditry in the Zamfara State of Nigeria: Opportunities and Challenges (UINSI Samarinda, 2021)
The paper investigates the armed banditry that engages in the highway robbery attacking villagers and travelers in the Zamfara state of Nigeria. The paper aimed at examines hirāba in Islamic criminal law and the penal code of the state for the possibility of applying the provisions to curb armed banditry in the state. The paper is a Sharia study; thus, the descriptive-analytical method was followed. Opinions of four Sunni schools are relied on in most cases. In addition, academic works of contemporary jurists and thinkers in journals were extensively consulted. The critical studies of jurist’s definitions of hirāba revealed that the crime of hirāba comprises maritime piracy, aircraft hijacking, armed banditry, kidnapping, and any act of destroying society. Zamfara state, which first reintroduced the Islamic criminal system, witnessed maximum security between 2000 and 2009 because there is a political will to enforce Islamic law. Although it is alleged that Sharia was supposed to bring joy but brought bandits to the state, while the study revealed that armed banditry started around 2009, sharia implementation is not responsible for the insecurity. The paper concludes that the practical solution is the enforcement of new Sharia in the region.